Activation of the alpha subunit of Gs in intact cells alters its abundance, rate of degradation, and membrane avidity (The Rockefeller University Press, 1992)
Binding of GTP induces alpha subunits of heterotrimeric G proteins to take on an active conformation, capable of regulating effector molecules. We expressed epitope-tagged versions of the alpha subunit (alpha s) of Gs in genetically alpha s-deficient S49 cyc- cells. Addition of a hemagglutinin (HA) epitope did not alter the ability of wild type alpha s to mediate hormonal stimulation of adenylyl cyclase or to attach to cell membranes. The HA epitope did, however, allow a mAb to immunoprecipitate the recombinant protein (HA-alpha s) quantitatively from cell extracts. We activated the epitope-tagged alpha s in intact cells by: (a) exposure of cells to cholera toxin, which activates alpha s by covalent modification; (b) mutational replacement of arginine-201 in HA-alpha s by a cysteine residue, to create HA-alpha s-R201C; like the cholera toxin-catalyzed modification, this mutation activates alpha s by slowing its intrinsic GTPase activity; and (c) treatment of cells with the beta-adrenoceptor agonist, isoproterenol, which promotes binding of GTP to alpha s, thereby activating adenylyl cyclase. Both cholera toxin and the R201C mutation accelerated the rate of degradation of alpha s (0.03 h-1) by three- to fourfold and induced a partial shift of the protein from a membrane bound to a soluble compartment. At steady state, 80% of HA- alpha s- R201C was found in the soluble fraction, as compared to 10% of wild type HA-alpha s. Isoproterenol rapidly (in < 2 min) caused 20% of HA-alpha s to shift from the membrane-bound to the soluble compartment. Cholera toxin induced a 3.5-fold increase in the rate of degradation of a second mutant, HA-alpha s-G226A, but did not cause it to move into the soluble fraction; this observation shows that loss of membrane attachment is not responsible for the accelerated degradation of alpha s in response to activation. Taken together, these findings show that activation of alpha s induces a conformational change that loosens its attachment to membranes and increases its degradation rate.